The effects of a parent’s guidance program about the frequency of their comments during competitions (Brazilian Journal of Behavioral and Cognitive Therapy, 2014)
This article developed and evaluated the effects of an orientation program for parents regarding the frequency of comments during their children’s futsal competitions. The ones participating were parents of three children from the sub-eleven category. The study was divided into phases. In the baseline, the comments were recorded during the games. In the intervention, parents were individually instructed using the Cheering Parent’s Guide. The evaluation after the intervention was similar to the one got after the baseline. The comments were categorized and quantified into positive, negative and neutral. The results demonstrated that parents emitted more positive than negative comments during the matches. The most significant changes were the reinforcing and instructive comments. It was noticed that the score of the game interfered in the comment rate, in more competitive games, the rate of motivating comments and criticisms raised. Despite the parents agreed on the importance of the intervention, the results suggested that it was only effective to change some categories.
Keywords: Sports Psychology; Parents and Children; Futsal; Behavioral Analysis